Microfluidic formulation of nanoparticles for biomedical applications - Shepherd, Sarah J.; Issadore, David; Mitchell, Michael J. (Biomaterials, 2021)
Nanomedicine has made significant advances in clinical applications since the late-20th century, in part due to its distinct advantages in biocompatibility, potency, and novel therapeutic applications. Many nanoparticle (NP) therapies have been approved for clinical use, including as imaging agents or as platforms for drug delivery and gene therapy. However, there are remaining challenges that hinder translation, such as non-scalable production methods and the inefficiency of current NP formulations in delivering their cargo to their target. To address challenges with existing formulation methods that have batch-to-batch variability and produce particles with high dispersity, microfluidics—devices that manipulate fluids on a micrometer scale—have demonstrated enormous potential to generate reproducible NP formulations for therapeutic, diagnostic, and preventative applications. Microfluidic-generated NP formulations have been shown to have enhanced properties for biomedical applications by formulating NPs with more controlled physical properties than is possible with bulk techniques—such as size, size distribution, and loading efficiency. In this review, we highlight advances in microfluidic technologies for the formulation of NPs, with an emphasis on lipid-based NPs, polymeric NPs, and inorganic NPs. We provide a summary of microfluidic devices used for NP formulation with their advantages and respective challenges. Additionally, we provide our analysis for future outlooks in the field of NP formulation and microfluidics, with emerging topics of production scale-independent formulations through device parallelization and multi-step reactions within droplets.